Alternative Fish Food Production Technology: Case Study in Trenceng Village, Tulungagung Regency - Samudro, Bhimo Rizky; Soesilo, Albertus Maqnus; Pratama, Yogi Pasca; Prasetyo, Andri (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The development of ornamental fish feed technology plays a crucial role in ensuring the long-term viability of fisheries in Trenceng Village, Sumbergempol, and Tulungagung Regency. The objective is to develop alternative technology for manufacturing fish feed that may effectively reduce production expenses and fulfil the requirements of ornamental fish growers. Method: The approach promotes self-sufficiency among ornamental fish producers in producing fish feed. This is done in response to the declining pricing of ornamental fish and the comparatively high feed cost. Practical Applications: This technology's practical application is to create food self-sufficiency for ornamental fish farmers in terms of ease of price access and physical. Conclusion: Ornamental fish farmers are anticipated to benefit from implementing alternative fish feed technologies, as it will assist them in managing volatility and reductions in product revenue. Therefore, this technology can enhance the sustainability of fisheries in Trenceng Village, Sumbergempol, and Tulungagung Regency.